08.36: Numerical modelling of circular CFST members and assessment of multi‐axial stress state effects. (13th September 2017) - Jiang, Yadong; Kalemi, Bledar; Silva, António; Castro, José Miguel; Monteiro, Ricardo
ABSTRACT: Multi‐axial stress states, namely the concrete confinement effect and the bi‐axial stress state that develops on the steel profile, have a significant influence on the flexural behaviour of the circular Concrete‐Filled Steel Tubular (CFST) members. The results from an experimental investigation carried out at the University of Porto indicated that the combination of the two multi‐axial stress states contributes to an increase of the flexural capacity of circular CFST members. This paper presents the development of a 3D model in ABAQUS that has been validated against experimental data. A distributed plasticity model is also developed in OpenSees. It is shown that the 3D model, contrary to the distributed plasticity model, is able to simulate the multi‐axial stress states, hence reproducing the bending behaviour of circular CFSTs with fairly good accuracy. An extensive parametric study involving different CFST members is conducted with the aim of characterizing the concrete confinement effects as well as the bi‐axial stress states developing in the steel tube. A large database of results was generated and then employed in the derivation of modified uniaxial material strength properties. Relationships between the corrected material strength and the cross‐section factor, ζ, which depends on the cross‐section properties of the member, for both concrete and steel section, were derived as closed‐form expressions. These properties can be adopted both for cross‐section analysis and for the development of simplified distributed plasticity models. The accuracy of the distributed plasticity model was improved when the strength correction equations were applied.